2017
DOI: 10.1177/2325967117712685
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Testing of 3 Medial Patellofemoral Ligament Reconstruction Techniques

Abstract: Background:Several techniques are available to secure the graft to the patella during medial patellofemoral ligament (MPFL) reconstruction. The biomechanical properties of these techniques remain unknown.Purpose:To compare the biomechanical properties of 3 MPFL patellar fixation techniques: bone tunnels (BT), PushLock anchors (PL), and tenodesis screws (TS).Study Design:Controlled laboratory study.Methods:Forty-five MPFL reconstructions were performed using 3 different reconstruction techniques (BT, PL, and TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…These studies are summarized in Table 1 . 4 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18
Fig 1 Preferred Reporting Items for Systematic Reviews and Meta-Analyses flowchart detailing the database search and inclusion/exclusion process. (MPFL, medial patellofemoral ligament.)
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are summarized in Table 1 . 4 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18
Fig 1 Preferred Reporting Items for Systematic Reviews and Meta-Analyses flowchart detailing the database search and inclusion/exclusion process. (MPFL, medial patellofemoral ligament.)
…”
Section: Resultsmentioning
confidence: 99%
“…Of the 6 studies that evaluated patellar fixation, all 6 reported on ultimate load to failure and 5 commented on stiffness. 4 , 11 , 12 , 13 , 14 , 15 Of the 3 studies that evaluated femoral fixation, all 3 studies commented on ultimate load to failure and 2 commented on stiffness. 16 , 17 , 18 …”
Section: Methodsmentioning
confidence: 99%
“… 10 In another study, it was reported that patellar fixation performed with anchor fails easier than the patellar bone tunnel. 11 Zanon et al. reported a surgical technique in double-bundle MPFL reconstruction using a single patellar tunnel directed toward the cranial direction.…”
Section: Discussionmentioning
confidence: 99%
“…10 In another study, it was reported that patellar fixation performed with anchor fails easier than the patellar bone tunnel. 11 Zanon et al reported a surgical technique in doublebundle MPFL reconstruction using a single patellar tunnel directed toward the cranial direction. 3 In the technique reported by the authors, the lateral end of the patellar tunnel is opened to the superior pole, where the weaker bone is located.…”
Section: Discussionmentioning
confidence: 99%
“…8,24,28 Multiple prior studies have reported the biomechanical properties of these fixation methods on the patellar side. 13,19,22,26,27 Adequate graft fixation to the femur is also critical to preventing the laxity of the reconstructed MPFL. Femoral fixation is commonly performed using an IS placed at the MPFL insertion point defined by Schöttle et al 29 However, the IS method of femoral fixation has some possible disadvantages, including the potential for injury to the distal femoral physis, which can lead to iatrogenic growth alteration and ultimately result in angular growth deformities.…”
mentioning
confidence: 99%